GPER‐regulated lncRNA‐Glu promotes glutamate secretion to enhance cellular invasion and metastasis in triple‐negative breast cancer. Issue 3 (6th February 2020) - Yin, Jiali; Tu, Gang; Peng, Meixi; Zeng, Huan; Wan, Xueying; Qiao, Yina; Qin, Yilu; Liu, Manran; Luo, Haojun
Abstract: Triple‐negative breast cancer (TNBC) is a group of breast cancer with heterogeneity and poor prognosis and effective therapeutic targets are not available currently. TNBC has been recognized as estrogen‐independent breast cancer, while the novel estrogen receptor, namely G protein‐coupled estrogen receptor (GPER), was claimed to mediate estrogenic actions in TNBC tissues and cell lines. Through mRNA microarrays, lncRNA microarrays, and bioinformatics analysis, we found that GPER is activated by 17β‐estradiol (E2) and GPER‐specific agonist G1, which downregulates a novel lncRNA (termed as lncRNA‐Glu). LncRNA‐Glu can inhibit glutamate transport activity and transcriptional activity of its target gene VGLUT2 via specific binding. GPER‐mediated reduction of lncRNA‐Glu promotes glutamate transport activity and transcriptional activity of VGLUT2. Furthermore, GPER‐mediated activation of cAMP‐PKA signaling contributes to glutamate secretion. LncRNA‐Glu‐VGLUT2 signaling synergizes with cAMP‐PKA signaling to increase autologous glutamate secretion in TNBC cells, which activates glutamate N‐methyl‐D‐aspartate receptor (NMDAR) and its downstream CaMK and MEK‐MAPK pathways, thus enhancing cellular invasion and metastasis in vitro and in vivo. Our data provide new insights into GPER‐mediated glutamate secretion and its downstream signaling NMDAR‐CaMK/MEK‐MAPK during TNBC invasion. The mechanisms we discovered may provide new targets for clinical therapy of TNBC.